POTENSI PERKEBUNAN RAMBUTAN BERDAMPAK PADA EKONIMI MASYARAKAT DI DESA PETLENG - Silpa Maiko; Safry Musa Malaka; Siria Mei Kamutlaka; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
This study aims to identify the plantation potential in Petleng Village, Alor Tengah Utara District, Alor Regency, to analyze the challenges and constraints faced by farmers, and to formulate solutions and development strategies for the plantation sector in the village. A qualitative approach using in-depth interview methods with farmers in Petleng Village was employed to collect data. The results indicate that Petleng Village has significant potential in the plantation sector, particularly in agriculture, with nearly 65% of its total area consisting of paddy fields. This condition positions the village as a potential center for high-quality rice production as well as an educational agro-tourism village. However, farmers face several challenges, including inequitable distribution of agricultural subsidies, drought, and difficulties in irrigation, which have led to decreased yields and even crop failure. The proposed solutions include improving irrigation systems and water resource management, adopting modern agricultural technologies, diversifying plantation products, developing partnerships, and encouraging community participation in the management and development of educational agro-tourism. This study provides comprehensive insights into the potential, challenges, and solutions for developing the plantation sector in Petleng Village; however, further feasibility studies are required to assess the socio-economic and environmental impacts of implementing these solutions.Keywords: agriculture, potential, development, Petleng village